Penggunaan Platform Youtube Kanal Arab Podcasts Untuk Meningkatkan Keterampilan Maharah Kalam di MTs Negeri 3 Malang - Ummah, Silviyah Mashlahatil; Syafril R, Raihan Ammar; Fikri, Shofil (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2024)
Language is a social communication tool in the form of a system of sound symbols produced from human speech. Over time, language has developed in terms of sound, structure, meaning, style and even teaching and learning. In today's digital era, technology can be used as an innovative, creative, effective and efficient learning medium. Social media is one tool that can be used as a learning medium in language learning. YouTube is a media that can be used as a language learning medium. This research aims to analyze learning media using the YouTube Arab Podcasts platform in Arabic language learning in the form of discussions using the book takalam al-arabiyah volumes 1 and 2 of daily life topics for beginners, muhadatsah arabiyah, and nadzom alfiyah Ibnu Malik.. This research method using library research using a descriptive qualitative research approach method. The data sources for this research come from books, articles and content on the Arab Podcasts YouTube channel. The data collection technique is an analysis of the Arab Podcasts YouTube channel. Data analysis is carried out in three ways, namely data presentation, data reduction and conclusion drawing. The results of this research show that the YouTube Arab Podcasts platform is one of the Arab language learning media that is easy for students to understand. Keywords: youtube, arab podcast channel, arabic language learning